Current Strategies for the Development of a Therapeutic Cancer Vaccine – A Review - R Bhaliya, Krupa; Anwer, Muneera; Q Wei, Ming (Eastern Journal of Medical Sciences, 2024)
The lack of effective cancer immunotherapies over the last few decades has led to the development of novel strategies in the field of therapeutic cancer vaccines. Hence, it could be argued that therapeutic cancer vaccines are on the verge of becoming primary immunotherapy for cancer. Such vaccines have undergone many transformations in the last decade. However, little is known about the biological and technological aspects of cancer vaccines. Improved understanding of tumor-specific antigens and novel delivery systems facilitate improved cancer vaccine design. The main goals of a cancer vaccine should be tumor deterioration, eradication of residual tumors, long duration of antitumor memory, and avoidance of adverse effects. These goals could be attained by improving biology and platform-based strategies for cancer vaccines. This review summarizes various biology and platform-based strategies from preclinical and clinical studies of therapeutic cancer vaccines.